ANALISIS KEPATUHAN DAN TRANSPARANSI PELAPORAN DANA KAMPANYE PEMILU 2024 DI KABUPATEN SIDOARJO PARTAI X - Haqi, Cinta Anasilla Wulan; Rida Perwita Sari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The KPU in Indonesia, including East Java Province, released audit findings covering the acquisition and use of campaign funds by political parties. This analysis aims to analyze the extent to which political parties comply with compliance and how transparent their campaign fund reporting is. The subject of the investigation is Party X. Based on the survey results, the 50 election participants generally showed a high level of compliance, although there were some exceptions. This is also reflected in the requirement to submit audit results through the official website of the General Election Commission (KPU) of Party X in East Java Province.